Exploring the biocontrol and plant growth-promoting potential of Streptomyces kronopolitis isolate SA18 against durian foliar blight and dieback disease - PARINYA KRAIVUTTINUN; KUNCHIT PIRAPAK; PATTACHAI PINNAK; WANWISA PIRAPAK (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kraivuttinun P, Pirapak K, Pinnak P, Pirapak W. 2024. Exploring the biocontrol and plant growth-promoting potential of Streptomyces kronopolitis isolate SA18 against durian foliar blight and dieback disease. Biodiversitas 25: 2661-2669. Actinomycetes have been extensively studied for their potential as plant growth promoters and biocontrol agents against fungal plant pathogens. In Thailand, durian is a highly valuable fruit crop, celebrated for its delectable fleshy arils. Rhizoctonia solani destruction causes foliar blight and dieback, a severe disease on durian plantations. Our investigation objective was to isolate, select, and identify actinomycetes that exhibit antagonistic properties and could improve the growth of durian. This study revealed that 37 actinomycete isolates were obtained, comprising 14 endophytic isolates and 23 soil-derived actinomycete isolates from durian plantations in Thailand's Uttaradit and Sukhothai Provinces. All actinomycete isolates demonstrated the ability to inhibit pathogen growth through in vitro antagonistic bioassay. Isolate SA18 exhibited the highest percentage inhibition of radial growth against R. solani isolate 01, achieving an impressive 92% inhibition. Furthermore, isolate SA18 demonstrated the capacity to produce 5.91 ?g/mL of indole acetic acid after seven days of culture, increasing to 45.72 ?g/mL after 14 days. This isolate also exhibited phosphate solubilization ability. In the detached leaf bioassay, isolate SA18 effectively controlled the spread of fungal pathogens, reducing disease severity significantly from 93.75% in the control treatment to 53.75% with a concentration of 108 spores/mL of isolate SA18. Morphological examination and 16S rRNA gene sequencing revealed that isolate SA18 formed smooth-surfaced spores in chains and showed a close relationship with Streptomyces kronopolitis based on the 16S rDNA sequence. This study is the first to report the presence of S. kronopolitis in soil samples collected from durian orchards in Thailand. This isolate can improve plant growth and control R. solani in bioassays. S. kronopolitis isolate SA18 can potentially be a biocontrol agent for durian plantations.